Precision Imprinted Nanostructural Wood. Issue 48 (8th October 2019) - Huang, Dafang; Wu, Jiayang; Chen, Chaoji; Fu, Xinxin; Brozena, Alexandra H.; Zhang, Yan; Gu, Ping; Li, Chen; Yuan, Changsheng; Ge, Haixiong; Lu, Minghui; Zhu, Mingwei; et al.
Abstract: Wood is a ubiquitous material, widely used in human society, that features naturally abundant, aligned longitudinal cells (e.g., tracheids in softwood and fibers/vessels in hardwood) with diameters of ≈50–1000 µm. Here, the realization of, fine patterns on a wood surface ranging in size from 40 nm to 50 µm by precision imprinting is described. The precision imprinting is enabled by releasing cellulose fibril aggregates from the bondage of lignin through the delignification process, then imprinting in wet condition and fixing the designed configuration in the dry state. Various precision structures on a wood surface using imprinting technology, including dot arrays, lines, triangular features, and other complex patterns, are successfully demonstrated. Even multiscale structures with nanosized lines on the surface of micrometer hemiballs can be acquired. As a proof of concept, the use of surface‐imprinted wood as a microlens array (MLA), which exhibits superior imaging ability and thermal stability even at a high temperature up to 150 °C compared with traditional polystyrene MLA, is demonstrated. This precision imprinted wood may open new possibilities toward environmentally friendly devices and applications in optics, biology, electronics, etc. Abstract : Imprinted wood with fine patterns on the wood surface ranging from 40 nm to 50 µm in size is fabricated by precision imprinting. Complex patterns of dot arrays, lines, triangular features, and even multiscale structures are successfully generated. This precision imprinted wood may offer new opportunities toward environmentally friendly devices in optics, biology, electronics, etc.